The Great Italian Masquerade. Issue 2 (4th March 2021) - Miranda, Laura; Gilani, Sarwat; Han, Liying; Epelbaum, Oleg
ABSTRACT: Tuberculosis and sarcoidosis are both granulomatous diseases centered on the lung but capable of myriad extrapulmonary manifestations. Because of substantial similarity in their presentations, these two entities can be notoriously challenging to differentiate. This can be particularly true of countries in which tuberculosis is rarely encountered because of a reflexive tendency to ascribe granulomatous inflammation in the lung to sarcoidosis, especially if the granulomas are non-necrotizing. However, as our case from a non-endemic country reminds, sarcoidosis can be comfortably diagnosed only after convincing exclusion of infectious causes of granulomas. Distinguishing these two diseases is of utmost importance as, despite their overlapping presentations, they have completely non-overlapping treatments which can lead to harm if erroneously applied. At the end of our discussion, we summarize the clinical features favoring one diagnosis over the other.